Alasan-alasan Penolakan Pengunduran Diri Pemerintah Bashar Al-Assad terhadap Tuntutan Oposisi dalam Gerakan Reformasi Suriah - Fitri Astutui; Harmiyati Harmiyati (Jurnal Paradigma, 2012)
Syria is among the Arab states affected by the storm of revolution. Syrian political conflicts are not purely due to internal problems in the country, but Syrian political conflict is a scenario that has been designed for the United States and its Allies topple Bashar al-Assad’s government. People Power is generally driven by the political consciousness of a country’s domestic problems, but the ongoing conflict in Syria is the demands made by the opposition is driven from the outside. The existence of power from the outside to intervene in Syria that sparked opposition to demand the president to immediately step down from the chairmanship.President Bashar al-Assad has the authority under the constitution. Based on the inherent authority of the constitution and the constitution of Syria, Bashar al-Assad has the authority to resolve the conflict in Syria. By legitimacy, Bashar al-Assad has the authority to stay in power because of the support of its people. A president could not have done anything without the institutions efforts and support of all the people. Besides large countries such as Russia, China and Iran plays an important role in the rejection of the resignation of Bashar al-Assad to the demands of the Syrian opposition.